Effects of Blidingia sp. Extract on Intestinal Inflammation and Microbiota Composition in LPS-Challenged Mice - Song, Wei; Li, Yan; Zhang, Xuelei; Wang, Zongling (Frontiers in Physiology, 2019)
Blidingia sp is a green alga that has spread rapidly in Subei Shoal in China. To explore the potentially beneficial effects of Blidingia sp, we investigated the anti-inflammatory activity of water–methanol extract of Blidingia sp in a mouse model of LPS-induced intestine inflammation. The results showed that administration with extract of Blidingia sp significantly alleviated LPS-induced increases of inflammatory cytokines content in serum, as well as gene expression of inflammatory cytokines in ileum. Moreover, extract of Blidingia sp inhibited the phosphorylation of NFκB and IκBα proteins in LPS-challenged mice. In association with these changes, extract of Blidingia sp also prevented mice from intestinal morphology damage and cell apoptosis. Interestingly, extract of Blidingia sp also showed beneficial effects on caecal microbiota diversity and composition in LPS-challenged mice. In conclusion, our results suggested that extract of Blidingia sp play beneficial effects on the recovery of intestinal function via alleviating inflammatory response, improving the maintenance of intestinal morphology and decreasing cell apoptosis in LPS-induced intestine inflammation. In addition, its beneficial effects on caecal microbiota composition may play a role in its anti-inflammatory activity. Our results suggested that extract of Blidingia sp could be potentially used for the prevention of intestine inflammation.